2018
DOI: 10.1093/infdis/jiy600
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Prevalence Among American Indian Women of the Great Plains

Abstract: Background. High-risk human papillomavirus (hrHPV) causes cervical cancer. In the United States, approximately 40% of women aged 14-59 years from all racial and ethnic groups are infected with HPV, and prevalence typically declines with age. However, American Indian (AI) women are insufficiently sampled to permit a population-specific estimate of hrHPV prevalence.Methods. Vaginal swabs were self-collected by 698 AI women aged 21-65 years from a tribal community in the Great Plains. We estimated the population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…More recently, the Pap screenings were augmented with the HPV vaccine and hrHPV type-specific testing. However, despite the decline, U.S. cancer registries with linkage to Indian Health Service (IHS) records showed a 25% higher rate of cervical cancer incidence and mortality in Native women when compared with Hispanic non-white women, with a nearly two-fold variation across IHS regions [ 6 , 7 , 8 ]. Several studies also showed that, for most U.S. regions, cervical cancer mortality rates among Native women are consistently higher than those for all other races [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the Pap screenings were augmented with the HPV vaccine and hrHPV type-specific testing. However, despite the decline, U.S. cancer registries with linkage to Indian Health Service (IHS) records showed a 25% higher rate of cervical cancer incidence and mortality in Native women when compared with Hispanic non-white women, with a nearly two-fold variation across IHS regions [ 6 , 7 , 8 ]. Several studies also showed that, for most U.S. regions, cervical cancer mortality rates among Native women are consistently higher than those for all other races [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, among two separate studies in Native American women, HPV-16 was the least prevalent. Alarmingly, HPV-51 was the most prevalent among Native women and is not covered by the current HPV vaccines [ 7 , 13 ]. Since the introduction of the HPV vaccines, hrHPV prevalence decreased among women eligible for vaccination, specifically for HPV-16 and -18 [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the next most frequent causes of death in AI/ANs are quite different from the general population, with intentional or unintentional injury, diabetes, and chronic liver disease among the next most common ( Espey et al, 2014 ). Another example highlighting the importance of AI/AN participation in research was a study of high-risk Human Papillomavirus Virus (hrHPV) in AI women where Lee et al found that the single most prevalent hrHPV genotype (HPV-51) was quite different from the prevalence in the general population, and this genotype was not covered by the extant HPV vaccines ( Lee et al, 2019 ). This information, which directly impacts health care and cancer prevention, was uncovered only because of participation by a large number of AI women and their willingness to donate biospecimens.…”
Section: Introductionmentioning
confidence: 99%
“…Contrarily, high-risk HPV (HR-HPV) type cause cervical, anal, and other genital cancers, which could be detected in 99% of cervical cancers-the second most common cancer in women worldwide. HPV16 and -18 have been found to be the most pathogenic of the HR-HPV types, causing about 70% of cervical cancers worldwide [7][8][9][10]. Of note, most HPV infections are completely asymptomatic, resulting in a delay in diagnosis and follow-up treatment with disastrous consequences [11].…”
Section: Introductionmentioning
confidence: 99%